Bounded rationality and the adoption of weather index insurance: Evidence from an extra-laboratory experiment with farmers in Germany. Issue 1 (5th February 2018) - Mußhoff, Oliver; Hirschauer, Norbert; Grüner, Sven; Pielsticker, Stefan
Abstract : Purpose: The purpose of this paper is to check which role-bounded rationality might play as an explanation for farmers' missing willingness to adopt weather index insurance (WII). WII is an innovative risk management instrument that causes low administration and regulation costs. Moreover, index insurance is plagued neither by moral hazard nor by adverse selection. Nonetheless, WII has been little used to date in agriculture. Design/methodology/approach: An extra-laboratory experiment in the form of a multi-period, single-person business simulation game is conducted with farmers as experimental subjects to investigate the reasons for the low willingness to adopt WII. Findings: First, the demand for WII decreases as the premium loading increases. Second, a transparent communication of the loading reduces demand, indicating that farmers refrain from transactions if they feel that the other party earns (too) much money. Third, communicating to farmers that the index insurance has been subsidized raises demand even though insurance costs in terms of loading are kept constant. This can be taken as an indication that farmers interpret subsidies as a signal for profitable action. Originality/value: Using an experimental approach and going beyond observational research, this study investigates the prominent question of farmers' risk management and innovation adoption behavior, and, in particular, the behavioral effect of subsidies. Using a randomized controlled trial, the real behavior of real subjects with real incentives is studied under controlled experimental conditions. Compared to prior studies, the external validity of the experiment is improved by recruiting farmers instead of a convenience group of students.